SUCCESSION BETWEEN BILATERAL AND UNILATERAL BROTHERS PRESENT IN ART. 1841 OF THE CIVIL CODE - Detman, Giselle; Nunes da Vitória, Marcela; Bimbato Vieira, Victória (Revista Gênero e Interdisciplinaridade, 2021)
The 1988 Constitution brought as one of the main principles that all citizens are equal before the law. In consequence, it ensures the equality between sons, through the principle of family equality. However, the 2002 Civil Law, regarding the succession between unilateral and bilateral brothers, on the inheritance division, it was deternined that bilateral brothers should receive a bigger share than the unilateral brother, seeing that the Constitution does not talks about this matter. Should the article 1841 from the 2002 Civil Law be changed to guarantee tue equality on the sucession between unilateral and bilateral brothers?